Increasing Returns and Economic Geography - Krugman, Paul (Journal of Political Economy, 1991)
This paper develops a two-region, two-sector general equilibriun model of location. The location of agricultural production is fixed, but ionopolistcally competitive manufacturing finns choose their location to maximize profits. If transportation costs are high, returns to scale weak, and the share of spending on manufactured goods low, the incentive to produce close to the market leads to an equal division of manufacturing between the regions. With lower transport costs, stronger scale economies, or a higher manufacturing share, circular causation sets in: the more manufacturing is located in one region, the larger that region's share of demand, and this provides an incentive to locate still more manufacturing there. Thus when the parameters of the economy lie even slightly on one side of a critical "phase boundary", all manufacturing production ends up concentrated in only one region.